Middle Eastern mangroves at the arid limit (Red Sea and Arabian/Persian Gulf): eco-biophysical dynamics, blue-carbon MRV, climate-risk pathways, and governance for resilient restoration - a comprehensive review - Meraj, Gowhar; Abouleish, Mohamed Yehia; Ali, Tarig; Hashimoto, Shizuka; Marazi, Asif; Chakrabortty, Rabin; Singh, Suraj Kumar; Kanga, Shruti; Almazroui, Mansour; Bhuyan, Md. Simul (Frontiers in Marine Science, 2025)
Middle Eastern (ME) mangroves, spatially restricted and fragmented at the arid limit of the biome, underpin shoreline protection, fisheries, and blue-carbon initiatives along rapidly urbanizing coasts. However, global generalisations tend to overestimate their functional capacity, risking context mismatched restoration and overestimated offset potential. We conducted a comprehensive multi-method review across the Red Sea, Arabian/Persian Gulf, and adjoining shores. From peer-reviewed and agency sources, the literature was synthesized across four domains: eco-biophysical dynamics, socio-economics, climate-risk pathways, and governance. The review demonstrated that four primary controls govern distribution and function: freshwater inputs, hypersalinity, heat, and sheltering geomorphology. Avicennia marina dominates as dwarf, slow-growing stands of 2–4 m, allocating resources below ground on carbonate and nutrient-poor substrates. Vertical accretion is modest 1–3 mm yr-¹, organic carbon burial is low 10–15 g C m-² yr-¹, and soil stocks are small 43 ± 5 Mg C ha-¹ relative to the humid tropics. A wave-energy threshold and micro- to mesotidal ranges constrain the flushing. Sea-level rise (SLR) of 2.92 mm yr-¹, with a projected increase of 39.1 cm by 2100, combined with thermal and salinity extremes, dust burial, and oiling, raises the risk. However, undisturbed soils confer high carbon permanence. Socio-economic benefits, such as nursery support, shoreline defense, and cultural amenities, are large, but enforcement, monitoring, reporting, and verification (MRV), and co-management remain uneven. A region-specific framework is most essential. Priorities are to safeguard groundwater-fed refugia, secure retreat corridors, reduce local stressors, and implement stress-matched restoration that replicates resilient features, such as space, sediment, seepage, and shelter, while grounding mitigation in arid-zone MRV and avoided-loss accounting. This study provides a resilience–threat typology and integrated governance framework linking legal protection, climate-linked restoration, regional coordination, and inclusive co-management.